Nowe Horyzonty . pismo młodzieżowe, no. 12, 1987 - Lubowlitański, Andrzej; Giertych, Jędrzej; Giertych, Maciej; Giertychowa, Maria; Lassus, Arnaud de; Seyda, Marian; Bohunowicz, Jerzy ([s.n.], 1987)
Creation and circulation: From issue no. 1=27(1991) published legally